Perancangan Aplikasi Game Edukasi Matematika Untuk Anak SD Menggunakan Metode Permainan Quiz Interaktif - Prastyo Aji, Dimas; Nugroho, Agus; Setiawan, Roby (Jurnal Informatika Dan Rekayasa Komputer(JAKAKOM), 2024)
Games have become a means of entertainment based on multimedia that is most in demand by the public, especially among young children today. This is the factor that drives many game developers to innovate with game products that have a positive impact on their fans. This research aims to contribute to the world of games, especially games that are educational for children who attend elementary schools. The educational side of this game is learning math quizzes that are simple and interesting. In this game, players can enjoy a quiz game based on the Android platform which at the same time adds knowledge and learning to count by answering questions in the educational game. Scores will be obtained based on the number of correct answers. This game aims to improve children's learning abilities, especially elementary school students grades 1 to 3 and increase understanding of how to calculate mathematics. The results obtained in this study are interactive and interesting games that can help students improve understanding and reduce boredom in learning mathematics.